The agility shift : creating agile and effective leaders, teams, and organizations - Pamela Meyer (Bibliomotion, Inc, 2015)
"The Agility Shift shows business leaders exactly how to make the radical mindset and strategy shift necessary to create an agile, entrepreneurial organization that can innovate and thrive in complex, ever-changing contexts"
Keywords: Agile Management (HRM2072-N)